Job Creation and Persistence in Services and Manufacturing - Catherine Armington; Zoltán J. Ács (Max Planck Institute for Research into Economic Systems, 2004)
An important new literature on gross employment flows has produced a great outpouring of stylized facts. In this paper we examine one aspect of this literature through the lens of dynamic models and theories of industrial evolution. We extend the Davis and Haltiwanger methodology for analysis of the persistence of gross job creation, distinguishing the persistence of new jobs from business births and from expansions. The persistence rates are then compared with those expected in each sector if average annual job creation and destruction were distributed across the business population independently of the prior year's changes. The results provide a basis for discussing aspects of the different dynamics of job creation in services and manufacturing.
Keywords: M13; L6; J6; L8; 330; Entrepreneurship; Industry Evolution; Job Flows; Services; Beschäftigung; Dienstleistungssektor; Verarbeitendes Gewerbe; Evolutionsökonomik; Theorie